2003
DOI: 10.1128/mcb.23.14.5090-5106.2003
|View full text |Cite
|
Sign up to set email alerts
|

Cdk5 Regulates the Organization of Nestin and Its Association with p35

Abstract: The intermediate filament protein nestin is characterized by its specific expression during the development of neuronal and myogenic tissues. We identify nestin as a novel in vivo target for cdk5 and p35 kinase, a critical signaling determinant in development. Two cdk5-specific phosphorylation sites on nestin, Thr-1495 and Thr-316, were established, the latter of which was used as a marker for cdk5-specific phosphorylation in vivo. Ectopic expression of cdk5 and p35 in central nervous system progenitor cells a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
166
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(180 citation statements)
references
References 44 publications
12
166
0
2
Order By: Relevance
“…44 Phosphorylation of nestin by different kinases leads to disassembly of nestin filaments during mitosis 44 or development of neuronal precursor cells. 45 This role of nestin during MC proliferation is further supported by the additional findings that nestin expression is clearly regulated during cell-cycle progression and that nestin knockdown by siRNA does affect cell-cycle progression in cultured MCs. In cultured MCs, nestin is markedly increased around nuclei of dividing cells and is strongly upregulated during S-and G2-phases compared with S1-phase.…”
Section: Nestin In the Injured Glomerulus C Daniel Et Alsupporting
confidence: 58%
“…44 Phosphorylation of nestin by different kinases leads to disassembly of nestin filaments during mitosis 44 or development of neuronal precursor cells. 45 This role of nestin during MC proliferation is further supported by the additional findings that nestin expression is clearly regulated during cell-cycle progression and that nestin knockdown by siRNA does affect cell-cycle progression in cultured MCs. In cultured MCs, nestin is markedly increased around nuclei of dividing cells and is strongly upregulated during S-and G2-phases compared with S1-phase.…”
Section: Nestin In the Injured Glomerulus C Daniel Et Alsupporting
confidence: 58%
“…18 However, Cdk5 is not restricted to neurons. It is also prominent in the testis, where its level is high but its function is unknown (our unpublished data), developing muscle, 19,20 bFGF-stimulated bovine aortic endothelial cell proliferation, 21 and differentiating monocytes. 22,23 Cdk5 is activated in dying cells, including both developing tissues (interdigital areas of mouse limbs, 24 differentiating rat lens, 4 and mouse brain 5 ) and adult tissues (regressing mouse prostate following androgen withdrawal and atrophic mouse ovaries 5 ).…”
Section: Introductionmentioning
confidence: 79%
“…Recent in vitro studies have shown that nestin can protect neural progenitors against oxidant-induced cell death through interaction with Cdk5 (Sahlgren et al, 2006). Indeed, nestin can serve as a scaffold for Cdk5 and is able to regulate its kinase activity in vitro (Sahlgren et al, 2003(Sahlgren et al, , 2006.…”
Section: Introductionmentioning
confidence: 99%